Who wants flexibility? Changing work hours preferences and life events - Robert William Drago; Mark Wooden; David Black (Institute for the Study of Labor (IZA), 2006)
We consider desires for flexibility in weekly hours by analyzing changes in work hours preferences using four years of data from the Household, Income and Labour Dynamics in Australia (HILDA) Survey. We control for work hours preferences in previous years and test for effects on desired labor force participation and, for those wishing to participate, on current hours preferences. Our findings reveal that, in general, women are more sensitive to life events than men. Women's preferred hours and labor force participation decline sharply with pregnancy and the arrival of children; their preferred hours approach usual levels as children enter school and ultimately decline as they become empty-nesters. We also find women's preferred hours increasing following separation but falling after divorce, with an opposing pattern for men. Finally, a sizeable minority of retirees have preferences for phased instead of full retirement.
urn:nbn:de:101:1-2009031352
Keywords: 330; Arbeitszeitflexibilisierung; Offenbarte Präferenzen; Arbeitskräfte; Lebensverlauf; Australien